Trace levels of peptidoglycan in serum underlie the NOD-dependent cytokine response to endoplasmic reticulum stress - Molinaro, Raphael (J Biol Chem, 2019)
NOD1 and NOD2 are intracellular sensors of bacterial peptidoglycan that belong to the Nod-like receptor family of innate immune proteins. In addition to their role as direct bacterial sensors, it was proposed that the nucleotide-binding oligomerization domain (NOD) proteins could detect endoplasmic reticulum (ER) stress induced by thapsigargin, an inhibitor of the sarcoplasmic or endoplasmic reticulum calcium ATPase family that pumps Ca(2+) into the ER, resulting in pro-inflammatory signaling. Here, we confirm that thapsigargin induces NOD-dependent pro-inflammatory signaling in epithelial cells. However, the effect was specific to thapsigargin, as tunicamycin and the subtilase cytotoxin SubAB from Shiga toxigenic Escherichia coli, which induce ER stress by other mechanisms, did not induce cytokine expression. The calcium ionophore A23187 also induced NOD-dependent signaling, and calcium chelators demonstrated a role for both intracellular and extracellular calcium in mediating thapsigargin-induced and NOD-dependent pro-inflammatory signaling, in part through the activation of plasma membrane-associated calcium release-activated channels. Moreover, our results demonstrate that both endocytosis and the addition of serum to the cell culture medium were required for thapsigargin-mediated NOD activation. Finally, we analyzed cell culture grade fetal calf serum as well as serum from laboratory mice using HPLC and MS identified the presence of various peptidoglycan fragments. We propose that cellular perturbations that affect intracellular Ca(2+) can trigger internalization of peptidoglycan trace contaminants found in culture serum, thereby stimulating pro-inflammatory signaling. The presence of peptidoglycan in animal serum suggests that a homeostatic function of NOD signaling may have been previously overlooked.